Systemic appropriation of social innovation in organizations from emerging markets: A proposal for the generation of shared value (2022)
More and more organizations in emerging markets have opted for corporate social innovation as a strategy to materialize their purpose and generate shared value. For this reason, the objective of this article is to propose a reference framework that allows organizations to understand and manage the elements and strategic enablers for the systemic appropriation of social innovation within, seeking to be adopted with greater capacity for action and consolidate. As a transversal and characteristic strategic element. To achieve this, a collective case study was carried out, in which, the need for organizations to have initial agreements in order to promote structural and systemic changes is evident. This provides a context to develop the mentality of social innovation in employees, while companies consolidate their capacity for social innovation, finding a balance between the formal and the emerging, the individual and the collective.